Nonlinear Approximation in the Large Deviations Principle - Oksana Yarova; Ya. I. Yeleyko (Statistics, Optimization & Information Computing, 2018)
The Markov random processes and their approximations are considered. The main object of study is the exponential generator of random processes with independent increments, which are the solution of the problems of large deviations. These processes satisfy the conditions that make it possible to consider the Poisson and Levy approximation. Generators of random processes are normalized by nonlinear parameters. Found an explicit form of normalization parameter estimation.